Modeling Languages for Multiagent Systems: A case study using AUML and MAS-ML - Campos, Juliana P.; Oliveira, Alcione de Paiva; Braga, José Luís (INFOCOMP Journal of Computer Science, 2010)
Agent Unified Modeling Language (AUML) and Multi-Agent System Modeling Language (MAS-ML) are modeling languages that extend Unified Modeling Language (UML) for modeling Multiagent Systems (MAS). This paper presents a comparison between these two languages achieved through a case study: a MAS that schedules lectures in conferences. The aim of this case study was to exemplify the usage of these languages, identify difficulties in modeling and carry out a comparison between the two extensions.